Magneto-optics of excitons interacting with magnetic ions in CdSe/CdMnS colloidal nanoplatelets - Shornikova, Elena V. (2021)
Excitons in diluted magnetic semiconductors represent excellent probes for studying the magnetic properties of these materials. Various magneto-optical effects, which depend sensitively on the exchange interaction of the excitons with the localized spins of the magnetic ions can be used for probing. Here, we study core/shell CdSe/(Cd,Mn)S colloidal nanoplatelets hosting diluted magnetic semiconductor layers. The inclusion of the magnetic Mn2+ ions is evidenced by three magneto-optical techniques using high magnetic fields up to 15 T: polarized photoluminescence, optically detected magnetic resonance, and spin-flip Raman scattering. We show that the holes in the excitons play the dominant role in exchange interaction with magnetic ions. We suggest and test an approach for evaluation of the Mn2+ concentration based on the spin-lattice relaxation dynamics of the Mn2+ spin system.